Predicting perceived police effectiveness in public housing: police contact, police trust, and police responsiveness - Torres, Jose Alexis (Policing and society, 2017)
Public housing authorities have implemented banishment policies giving police the authority to ban non-residents from public housing and arrest them for trespassing upon violating the ban. Scholars argue that banishment expands police powers because authorities need little reason to ban non-residents, are beyond judicial review, and can lead to racially disparate enforcement. However, it is unclear whether community policing may be able to mediate the negative effects of banishment, by building police trust, and still allow residents to perceive the police and banishment as effective. This study presents survey data from 221 public housing households in a Southeastern US city policed under banishment and community policing strategies. Regression analysis is used to test whether police contact, police trust, or police responsiveness can predict whether residents view the police as effective even in neighbourhoods where banishment is a commonly used policing tactic. Results indicate police trust and police responsiveness-under-policing or over-policing-to be the most significant predictors of perceived police effectiveness in public housing after controlling for police contact and demographic variables. Based on the findings, police officers in public housing should concentrate on gaining the trust of the community, which, in turn, can increase perceived effectiveness. However, banishment enforced in public housing can negatively affect perceived police effectiveness when residents perceive police to be over-policing or under-policing. Nonetheless, banishment can be a promising tool for public safety if used under the guidance of community policing.